DEVELOPING READING MATERIALS BY USING EDMODO FOR GRADE TENTH AT SMA NEGERI 11 MEDAN - Retno Kesuma Hati; Johannes Jefria Gultom (Universitas Negeri Medan, 2020)
The objective of this study was to develop reading materials by using Edmodo for grade tenth at SMAN 11 Medan. This study was conducted by using Research and Development design through six stages; gathering data and information, need analysis, designing materials and media, validating, revising (final product). The subject of the study was grade tenth of SMAN 11 Medan. The data were gathered by reviewing documents, conducting interview to English teacher and distributting questionnaire to X IPA 7 consists of 36 students to get the students’ need. The interview and questionnaire result prove that the students need the high order thinking reading materials and media. The developed reading materials were validated by two experts which are the average scores (4.55 and 4.05) show that the reading materials are valid and suitable to use for grade tenth students of SMAN 11 Medan. The result of product distributed to the students through edmodo.